Nutrition, Antioxidant and Organoleptic Activities Of Legen Drink (Borassus flabellifer L.) at Different Temperature And Storage Time - Sinta Dwi Puspita Sari; Fadjar Kurnia Hartati; Bambang Sigit Sucahyo; Retnani Rahmiati (CV. Media Digital Publikasi Indonesia, 2023)
Siwalan sap (Borassus flabellifer L.) is a liquid that comes out of the filter vessels as a result of cob tapping (bunches), both male and female flowers that have a sweet taste. Nira containing high sugar content, and nira ca experience the process of fermentation assisted by microbial activity. This study aims to determine the levels of reducing sugars, pH, total acids and antioxidant activity contained in legen drinks. In addition, to find out the best treatment related to the best temperature and storage time. This study uses a laboratory experimental quantitative analysis method. The research variables included temperature consisting of freezer temperature, refrigerator temperature, room temperature and storage period consisting of 12 hour, 24 hour and 34 hour. The data obtained were analysed based on parametric statistics using analysis of variance (ANOVA) using statistical product and service solution (SPPSS) version 24 and determining the best treatment using effectiveness tests. Temperature and long storage different influential very real to sugar reduction, pH, total acid and antioxidant activity. Interaction between temperature and different storage times had a significant effect on reducing sugars and had a very significant effect on pH, total acid and antioxidant activity. Based on the determination of the effectiveness test, it shows that the temperature 00C and long storage 24 hour and the best treatment with a yield value (NH) of 0,69 with the parameter is sugar reduction 3,98%, pH levels 2,57, total acid 3,83%, antioxidant activity (IC50) 12,24 g/ml, color 4,67 (neutral). Aroma 5,4 (like) and taste 5,16 (like).